AFFIRMATIVE ACTIONS: THE CASE OF THE URUGUAY SOCIAL CARD FOR TRANS POPULATION - Gainza, Patricia; González Viñoly, Patricia (Revista Sexología y Sociedad, 2016)
SIN CE 2010, URUGUAY HAS BEEN DEVELOPING PUBLIC POLICIES WITH A HUMAN RIGHTS PERSPECTIVE. IN THIS FRAMEWORK, AFFIRMATIVE ACTIONS HAVE BECOME A MEANS TO ACHIEVE RECOGNITION AND THE BEGINNING OF THE REDISTRIBUTION OF SOCIAL POWER FOR CERTAIN EXCLUDED GROUPS SUCH AS THE SEXUAL DIVERSITY GROUP. THIS ARTICLE NARRATES THE PROCESS OF PROVIDING SOCIAL BENEFITS THROUGH THE URUGUAY SOCIAL CARD (TUS, ITS SPANISH ACRONYM) FOR TRANS POPULATION IN URUGUAY. FIRST, IT DESCRIBES THE NEW URUGUAYAN SCENARIO REGARDING PUBLIC POLICIES IMPLEMENTED IN TERMS OF SEXUAL DIVERSITY AND, SECONDLY, THE GRANTING OF TUS-TRANS AS A FORM OF ACKNOWLEDGING THE RIGHTS OF THE POPULATION. THIRDLY, IT CHARACTERIZES THE TRANS POPULATION IN URUGUAY ACCORDING TO DATA PROVIDED BY THE PROGRAM ITSELF. FINALLY, IT ANALYZES THE SCOPE OF TUS-TRANS AS AN AFFIRMATIVE ACTION. KEY WORDS: PUBLIC POLICIES FOR SEXUAL DIVERSITY, AFFIRMATIVE ACTION, TRANS POPULATION, REDISTRIBUTION